Novel Pedicle Navigator Based on Micro Inertial Navigation System (MINS) and Bioelectric Impedance Analysis (BIA) to Facilitate Pedicle Screw Placement in Spine Surgery: Study in a Porcine Model. Issue 16 (15th August 2022) - Lin, Wentao; Xie, Faqin; Zhao, Shuofeng; Lin, Songhui; He, Chaoqin; Wang, Zhiyun
Abstract : Study Design: A porcine model. Objective: The study aims to design a novel pedicle navigator based on micro-inertial navigation system (MINS) and bioelectrical impedance analysis (BIA) to assist place pedicle screw placement and validate the utility of the system in enhancing pedicle screw placement. Summary of Background Data: The incidence of pedicle screw malpositioning in complicated spinal surgery is still high. Procedures such as computed tomography image-guided navigation, and robot-assisted surgery have been used to improve the precision of pedicle screw placement, but it remains an unmet clinical need. Methods: The miniaturized integrated framework containing MINS was mounted inside the hollow handle of the pedicle finder. The inner core was complemented by a high-intensity electrode for measuring bioelectric impedance. Twelve healthy male Wuzhishan minipigs of similar age and weight were used in this experiment and randomized to the MINS-BIA or freehand (FH) group. Pedicle screw placement was determined according to the modified Gertzbein–Robbins grading system on computed tomography images. An impedance detected by probe equal to the baseline value for soft tissue was defined as cortical bone perforation. Results: A total of 216 screws were placed in 12 minipigs. There were 15 pedicle breaches in the navigator group and 31 in the FH group; the detection rates of these breaches were 14 of 15 (93.3%) and 25 of 31 (80.6%), respectively, with a statistically significant difference between groups. The mean offsets between the planned and postoperatively measured tilt angles of the screw trajectory were 4.5° ± 5.5° in the axial plane and 4.8° ± 3.3° in the sagittal plane with the navigator system and 7.0° ± 5.1° and 7.7° ± 4.7°, respectively, with the FH technique; the differences were statistically significant. Conclusion: A novel and portable navigator based on MINS and BIA could be beneficial for improving or maintaining accuracy while reducing overall radiation exposure.